The Canadian Prospective Pragmatic Perilunate Outcomes (C3PO) trial; a protocol - Eric C. Mitchell; Isabelle Tottenham; Ruby Grewal; Matthew W. T. Curran; Neil J. White (BMC Musculoskeletal Disorders)
Abstract Background Perilunate spectrum injuries (PSI) are uncommon, but high-energy injuries that result in significant functional implications for patients. The existing literature on PSI is limited to small case-series and there are no evidence-based guidelines for management. Methods This manuscript outlines a protocol for a three-armed, national, multi-centre study, which includes a patient injury registry for PSI, as well as associated retrospective and prospective arms. The primary objective is to establish a national injury registry for patients who present with PSI. The secondary objectives are to examine the long-term clinical and radiographic outcomes of PSI, evaluate progression of these outcomes over time, and to examine the impact of specific operative and injury related factors on outcomes. Discussion This paper describes the protocol for a three-armed, multi-centre study of PSI. It outlines the rationale for the study as well as the relevant methodological details. An injury registry involving multiple centres is valuable given this is an uncommon injury with many potential variables affecting outcomes. Registry-based retrospective and prospective studies will benefit from the large clinical database provided by the registry and could be used to guide evidence-based treatment guidelines which are currently lacking in the literature. Trial registration Clinicaltrials.gov identifier: NCT04370626.